Who are robo-advisor users? - Seongsu David Kim; Marty Cotwright; Swarn Chatterjee (Journal of Finance Issues, 2019)
The purpose of this study is to explore the demand for robo-advising services by analyzing the participants' behavioral characteristics and investment patterns. With the 2015 Financial Industry Regulatory Authority Investor data, we found that robo-advisor users were younger investors with high risk tolerance, whose self-assessment of financial knowledge is comparatively higher than their actual knowledge, and were independent decision-makers. By controlling for those behavioral attributes of robo-advisor users, we also found that robo-advisor users were reluctant to invest in individual stocks, while they showed the largest preference for investing in pooled investment products such as Exchange Traded Funds. Implications of this study's findings can be beneficial to financial planning practitioners, academics, and regulators.
Keywords: D14; D91; G41; G51; G53; 330; Robo-advisors; Fintech; Financial Planning; Financial Literacy; Investing; Risk Tolerance